Education spending: more resources without management? - Carlos Renato de Melo Castro; Geraldo da Silva e Souza; Maria Eduarda Tannuri-Pianto (Economia Aplicada, 2017)
This paper models a cost function for the Brazilian public elementary school system. Methodologically, we use a Flexible Fourier Form to overcome the biases usually presented in the use of local flexible forms. The results indicate that, ceteris paribus, even spending 10% of the GDP with education would not be sufficient to meet the minimum proficiency for 100% of students. We observe that municipalities with higher income, less urban, better income distribution and higher illiteracy rates have higher spending requirements and higher levels of inefficiency. Among the variables that can be managed by the municipality administration are the number of students per class and the school hours per day. Finally, we obtained an average inefficiency rate of about 14.7%.